Perbandingan Metode Peluruhan untuk Memperkirakan Berakhirnya Gempabumi Susulan (Studi Kasus Gempabumi Signifikan di Wilayah Bali Tahun 2019-2020) - Soleh, Anggun Mohamad; Sukarasa, I Ketut; Gunawan, Tomy; Suarbawa, Komang Ngurah; Sumadiyasa, Made; Anggarani, Ni Kadek Nova (Kappa Journal, 2023)
An Data collection and processing has been carried out to compare the aftershock decay method which aims to determine the assumption of aftershock ending time, how much energy, fracture length and fracture velocity occurred on the island of Bali. Data processing using several methods, namely the Omori method, the Mogi method I, the Mogi II method, and the Utsu method. The data used is based on the BBMKG Region III Denpasar earthquake catalog book, that’s is case of the Buleleng earthquake on November 14 2019, the Jembrana earthquake on July 16 2019 and the South Kuta earthquake on March 19 2020. Based on the results of data processing, for the Buleleng earthquake case the method closest to the observations was the Mogi II method with the energy is 1012 joules, the fracture length is 1.186 m and the fracture speed is 29.78 m/s. As for the Jembrana and South Kuta earthquake cases, the results of the calculation of all methods have not come close to the observations. The magnitude of the energy, the length of the fracture and the fracture speed of the Jembrana earthquake is 3.562313 joules, 32.733 m, 327.330 m/s. Whereas for the South Kuta earthquake, the energy, fracture length and fracture velocity were 3.162317 joules, 125.890 m, 70.750 m/s